2017
DOI: 10.5301/jsrd.5000235
|View full text |Cite
|
Sign up to set email alerts
|

Complex Pathophysiology of Pulmonary Hypertension Associated with Systemic Sclerosis: Potential Unfavorable Effects of Vasodilators

Abstract: achieved in total PAH population, sub-analysis within CTD-PAH patients showed failure to achieve short-term primary endpoints (2-4). In addition, current PH registries, such as REVEAL and ASPIRE, showed that patients with SSc-PAH had worse prognosis than those with other PH subgroups (5, 6). Recent meta-analysis on prognosis of patients with SSc-PAH reported that 1-, 2-, and 3-year survival rates were 82%, 67%, and 56%, respectively, even in modern treatment era (7). Furthermore, a recent striking report has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…By contrast, in patients with an increased risk of left heart disease (low PVR and high PAWP) and/or restrictive lung disease (low TLC), the benefit of combination therapy was less pronounced. Therefore, in the ex-PAS population (an older subgroup of patients with more cardiovascular comorbidities),21 less benefit may be gained from combination therapy 22. Further research to determine the optimal treatment approach in addition to standard PAH therapies is required for this population.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in patients with an increased risk of left heart disease (low PVR and high PAWP) and/or restrictive lung disease (low TLC), the benefit of combination therapy was less pronounced. Therefore, in the ex-PAS population (an older subgroup of patients with more cardiovascular comorbidities),21 less benefit may be gained from combination therapy 22. Further research to determine the optimal treatment approach in addition to standard PAH therapies is required for this population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pulmonary arterial hypertension (PAH) is around 10% and, despite recent advances in the treatment armamentarium, PAH survival is still poor with a median survival time of 3 years [2]. Moreover, SSc-PAH patients are most often less responsive than patients with idiopathic PAH and have a worse prognosis, although they present with milder haemodynamic impairment [2][3][4][5]. However, recent studies have suggested that where aggressive therapy is used, a similar reduction in event rate is achievable in SSc and idiopathic PAH populations [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Calcinosis in scleroderma patients also comprises calcium hydroxyapatite and foamy macrophage clusters, similar histopathological characteristics to that found in HFTC/HHS calcinosis (9). However, there is no difference in serum calcium and phosphate levels between the two subgroups of scleroderma patients with and without symptomatic ectopic calcinosis (10). Furthermore, higher serum FGF23 levels correspond to increased ectopic calcinosis in female scleroderma patients (11).…”
Section: Discussionmentioning
confidence: 99%